Field effect transistor‐based tactile sensors: From sensor configurations to advanced applications. Issue 1 (2nd November 2022) - Wang, Jian; Xu, Shuyan; Zhang, Congcong; Yin, Ailing; Sun, Mingyuan; Yang, Hongru; Hu, Chenguo; Liu, Hong
Abstract: The past several decades have witnessed great progress in high‐performance field effect transistors (FET) as one of the most important electronic components. At the same time, due to their intrinsic advantages, such as multiparameter accessibility, excellent electric signal amplification function, and ease of large‐scale manufacturing, FET as tactile sensors for flexible wearable devices, artificial intelligence, Internet of Things, and other fields to perceive external stimuli has also attracted great attention and become a significant field of general concern. More importantly, FET has a unique three‐terminal structure, which enables its different components to detect external mechanics through different sensing mechanisms. On one hand, it provides an important platform to shed deep insights into the underlying mechanisms of the tactile sensors. On the other hand, these properties could in turn endow excellent components for the construction of tactile matrix sensor arrays with high quality. With special emphasis on the configuration of FETs, this review classified and summarized structure‐optimized FET tactile sensors with gate, dielectric layer, semiconductor layer, and source/drain electrodes as sensing active components, respectively. The working principles and the state‐of‐the‐art protocols in terms of high‐performance tactile sensors are detail discussed and highlighted, the innovative pixel distribution and integration analysis of the transistor sensor matrix array concerning flexible electronics are also introduced. We hope that the introduction of this review can provide some inspiration for future researchers to design and fabricate high‐performance FET‐based tactile sensor chips for flexible electronics and other fields. Abstract : This review focuses on FET‐based tactile pressure sensors. The working principles of this kind of tactile sensors are discussed in detail, the state‐of‐the‐art protocols for high‐performance tactile sensing are highlighted, and the major advances in large‐scale tactile sensor arrays and their applications in robotics, health care, and smart manufacturing in terms of transistor matrix are also introduced.